Asupan karbohidrat, serat, dan vitamin D dengan kadar glukosa darah pada pasien rawat inap diabetes mellitus - Zakiyah, Farida Farah; Indrawati, Veni; Sulandjari, Siti; Pratama, Satwika Arya (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2023)
The relationship between the blood glucose levels of diabetes mellitus patients and intake of carbohydrates, fiber, and vitamin DBackground: Diabetes Mellitus (DM) is a non-communicable disease with a combination of symptoms that appear in a person due to an increase in blood glucose levels (hyperglycemia) above average values. Good intake by following the guidelines for persons with diabetes, a nutritious diet that contains carbs, fiber, and vitamin D can help keep blood glucose levels within acceptable ranges. Objective: This study aims to the relationship between the blood glucose levels of patients at RSI Siti Hajar Sidoarjo and their intake of carbohydrates, fiber, and vitamin D. Methods: The method in this study was a quantitative study with a cross-sectional approach, the population in this study were DM patients who were hospitalized at RSI Siti Hajar Sidoarjo. The number of samples was estimated using the cross-sectional sample size calculation and the purposive sampling technique with 60 respondents. The patient's intake was measured using a 3x24 hour food recall questionnaire. Data were analyzed using the Chi-Square test. Results: The result showed that there was a relationship between carbohydrate intake and blood glucose levels (p=0.000) and fiber intake and blood glucose levels (p=0.003), but there was no significant relationship between vitamin D intake and blood glucose levels (p=1.00). Conclusion: Carbohydrate and fiber intake significantly correlated with the patient's blood glucose levels but not vitamin D intake.